Embodiment and Humiliation Moderation of Neural Responses to Others' Suffering in Female Submissive BDSM Practitioners - Luo, Siyang; Zhang, Xiao (Frontiers in Neuroscience, 2018)
Giving and receiving pain are common in the practice of BDSM (bondage-discipline, dominance-submission and sadism-masochism). Playing a submissive role during BDSM practice weakens both the behavioral and neural empathic responses of female individuals to others’ suffering, suggesting that long-term BDSM experience affects BDSM practitioners’ empathic ability. This study further investigates whether physical restriction during BDSM practice also modulates individuals’ neural responses to others’ suffering. We measured neural responses to others’ suffering by recording event-related potentials (ERPs) in female submissives while they viewed painful and neutral expressions in sexual sadistic/general social contexts under ball gag Blocking and Relaxed conditions. The neural responses recorded during 92-112 ms (N1), 132-172 ms (P2), 200-340 ms (N2), early late positive potential (LPP, 400-600 ms) and late LPP (700-1000 ms) were included in the analyses. Compared to the relaxed condition, when a ball gag was used to prevent facial muscle movement and facial mimicry, the N1, early LPP and late LPP responses neural responses to others’ suffering were inhibited. The moderation effect of ball gag blocking on the N1 and early LPP amplitudes was positively correlated with the subjective feelings of facial muscle stillness, and the blocking moderation effect on the late LPP amplitudes was positively correlated with subjective feelings of humiliation. This study is the first neuropsychological investigation of the transient BDSM-related physical restriction effects on BDSM practitioners. These findings suggest that physical restriction (via a ball gag) during BDSM practices increases the wearer's facial muscle stillness and sense of humiliation. This physical restriction inhibits both early automatic responses and late controlled processes in response to the suffering of others.